Surface correlation based indoor precise localization system in vulnerable environment with very few RF transmitters - Lee, J.H.; Lee, T. (Proceedings of the 32nd International Technical Meeting of the Satellite Division of the Institute of Navigation, ION GNSS+ 2019, 2019)
[No abstract available]